Reevaluating High-p Request Sequences: Uncovering the Complexities of a Low-Intensity Intervention for Challenging Behaviors - Maag, John W. (An Overview of Literature, Language and Education Research Vol. 10, 2025)
There has been an evolving and growing popularity of schools adopting multi-tiered systems of support (MTSS). Recent amendments to the Elementary and Secondary Education Act (ESSA) and reauthorization of the Individuals with Disabilities Education Act (IDEA) place emphasis on these approaches such as Response to Intervention (RtI) for academics and Positive Behavior Interventions and Supports (PBIS) to address students’ challenging behaviors. High-probability (high-p) request sequences, grounded in the principle of behavioral momentum, are an effective intervention for enhancing compliance and task completion among students who display challenging behaviors. Though widely regarded as a low-intensity strategy due to its presumed simplicity, this chapter highlights the nuanced complexities involved in its effective implementation. There are several subtleties for implementing high-p request sequences effectively that teachers would not automatically understand. Also, an examination of the research may raise concerns about how well this intervention translates into practice. The purpose of this chapter is to review empirical literature, discusses systematic reviews and meta-analyses, and introduces innovative techniques, such as embedding instructions, to enhance behavioral momentum. The chapter not only offers practical recommendations for educators and practitioners, but also to future researchers who may continue delving into the efficacy of high-p requests and, by doing so, also bridging the gap between research and application, and ensuring a more informed and impactful use of high-p request sequences.